2016
DOI: 10.1002/acr.22713
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Renal Impairment in Patients With Rheumatoid Arthritis: Results From a Cross‐Sectional Multicenter Study

Abstract: Objective. To assess the prevalence and associations of renal dysfunction in patients with rheumatoid arthritis (RA). Methods. COMEDRA is a French nationwide cross-sectional multicenter study on comorbidities in RA. Renal function was assessed from the estimated glomerular filtration rate (eGFR), using the Modification of Diet in Renal Disease equation. RA characteristics and risk factors for renal impairment were collected. Two logistic regression models, 1 with and 1 without the Framingham Risk Score, were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 25 publications
(26 reference statements)
4
25
0
3
Order By: Relevance
“…Chiu et al followed more than 12,000 RA patients for ve years in a cohort study, and they observed that diabetes, hypertension, hyperlipidemia, and cardiovascular disease were related to renal damage [36], which was consistent with the observations of Couderc et al [18] and Vansijl et al [14]. Unfortunately, we failed to nd an independent link between cardiovascular risk factors and kidney damage.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Chiu et al followed more than 12,000 RA patients for ve years in a cohort study, and they observed that diabetes, hypertension, hyperlipidemia, and cardiovascular disease were related to renal damage [36], which was consistent with the observations of Couderc et al [18] and Vansijl et al [14]. Unfortunately, we failed to nd an independent link between cardiovascular risk factors and kidney damage.…”
Section: Discussionsupporting
confidence: 89%
“…Another cross-sectional study of 107 RA patients and 76 patients with serum-negative arthritis observed renal impairment (GFR < 60 ml/min /1.73 m 2 ) in 17.48% of the patients with RA [9]. A multicenter cross-sectional survey involving 970 patients in France found that approximately 9% of patients with RA had impaired renal function, indicated by a GFR < 60 ml/min/1.73 m 2 [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…При этом следует учитывать, что оценку риска ССЗ и последующее лечение затрудняет «липидный парадокс», проявляющийся во взаимосвязи выраженного воспаления с уменьшением уровня липидов, правда, далеко не у всех больных [10,11]. Нельзя забывать и о патологии почек, которая наблюдаются у 8-15% больных РА и может нарастать в результате проводимого лечения, наличия амилоидоза или васкулита [12,13]. Однако сегодня практически отсутствуют специфические рекомендации по частоте мониторинга функции почек у больных РА, но имеются указания на необходимость ежегодной оценки уровня креатинина независимо от осуществляемого лечения.…”
unclassified
“…Однако сегодня практически отсутствуют специфические рекомендации по частоте мониторинга функции почек у больных РА, но имеются указания на необходимость ежегодной оценки уровня креатинина независимо от осуществляемого лечения. [12]. Амилоидоз -одно из наиболее тяжелых осложнений РА, которое наблюдается у 5-19% больных [14].…”
unclassified